PERAMALAN JUMLAH PENUMPANG KERETA REL LISTRIK JABODETABEK MENGGUNAKAN PROSES POISSON NONHOMOGEN - Dhea Amelia; Firdaniza Firdaniza; Kankan Parmikanti (LPPM Universitas Bina Bangsa, 2023)
The train is one of the alternative transportations for the community to carry out their activities in terms of work and tourism for long distances. One of the public transportation companies, namely, PT. Indonesian Commuter Train (KCI) is trusted as a provider of Electric Rail Trains (ERT) in order to optimally meet the needs of the community. The number of ERT passengers has an influence in planning the capacity of the train. For this reason, it is necessary to know the number of KRL passengers for the future. In this study we have forecasted the number of KRL passengers using the Nonhomogeneous Poisson process, where the intensity function is determined by a simple linear regression method. The results of forecasting the number of Jabodetabek ERT passengers using the Nonhomogeneous Poisson process, show that the number of Jabodetabek ERT passengers in November 2021 to April 2022 has decreased. The results of this forecasting fall into the fairly accurate category with a Mean Absolute Percentage Error (MAPE) value of 28%.